Positive teacher feedback and academic emotions among primary school children in China: A study within the control-value theory framework - Jianzhou Ni (International Journal of Educational Research Open)
Based on Pekrun’ s control-value theory, this study investigates the specific effects of positive teacher feedback (e.g., praise, classroom interaction, and academic support) on the academic emotions of Chinese primary school students in grades five and six. The study was conducted with 20 primary school grade 5 and 6 students (aged 10 to 13 years old) to analyse their emotional responses in different feedback contexts through a drawing task and semi-structured interviews. The results of the study showed that teachers’ praise helped enhance students’ pride and satisfaction, classroom interaction was effective in stimulating students’ interest and pleasure, and academic support boosted students’ confidence and eased their anxiety. These emotional responses not only enhanced students’ motivation to learn, but also strengthened the emotional bond between teachers and students. In addition, it was found that in the Chinese cultural context, students were more inclined to perceive teachers’ positive feedback as a recognition of their personal value. This study provides a new cultural perspective for the application of control-value theory and a useful reference for the design of classroom feedback strategies.